Performance Enhancement of NavIC With Low-Cost MEMS-IMU, Barometer, and Magnetometer - Saraswathi Sirikonda; Laxminarayana Parayitam; Hari B. Hablani (IEEE Access)
Integration of the global navigation satellite systems with the Inertial Navigation System (INS) is a sensor fusion stratagem for continuous and reliable navigation. Micro-electromechanical system (MEMS) based INS meets the high demand for low-cost autonomous navigation of land vehicles economically. However, their navigational performance degrades quickly, and their attitude estimation is poor. Therefore, other auxiliary sensors such as barometer, odometer and magnetometer have been used with integrated GNSS/INS to improve the accuracy of position, velocity and attitude estimates. When the MEMS-IMUs are integrated with the newly developed NavIC (Navigation with Indian Constellation) system, comprising seven satellites with a fair geometric dilution of precision, it may be challenging to provide the required navigation performance for land vehicles. Therefore, this paper examines the navigation performance of land vehicles using loosely coupled NavIC and MEMS-IMU augmented by a barometer and a three-axis magnetometer. The magnetometer is calibrated for accurate heading estimation, and bad measurements are identified by their excessive innovation and rejected. The performance of loosely coupled GPS/INS/Barometer/Magnetometer and NavIC+GPS/INS/Barometer/Magnetometer are compared. When aided by a barometer and a magnetometer, the achieved horizontal and vertical position accuracies ( $1σ $ ) for NavIC/INS are 1.96 m and 0.24 m; for GPS/INS, 0.53 m and 0.24 m; and NavIC+GPS/INS, 0.43 m and 0.23 m, respectively. The heading accuracy for all three systems is ~0.73°. This last ensemble of devices meets the required accuracy for identification of the lane for autonomous navigation of land vehicles in Indian urban areas, where the lane span is 3.75 m. However, further improvement in the accuracy is recommended.